The masterpiece ebook - Rivers, Francine (Tyndale Fiction, 2018)
A New York Times , USA Today , and Publishers Weekly bestseller “This character-driven romance will enthrall [Rivers’s] many fans.” ― Library Journal The New York Times bestselling author of Redeeming Love returns to her romance roots with this unexpected and redemptive love story, a probing tale with spiritual depth that reminds us that mercy can shape even the most broken among us into an imperfect yet stunning masterpiece. A successful LA artist, Roman Velasco appears to have everything he could possibly want―money, women, fame. Only Grace Moore, his reluctant, newly hired personal assistant, knows how little he truly has. The demons of Roman’s past seem to echo through the halls of his empty mansion and out across his breathtaking Topanga Canyon view. But Grace doesn’t know how her boss secretly wrestles with those demons: by tagging buildings as the Bird, a notorious but unidentified graffiti artist―an alter ego that could destroy his career and land him in prison. Like Roman, Grace is wrestling with ghosts and secrets of her own. After a disastrous marriage threw her life completely off course, she vowed never to let love steal her dreams again. But as she gets to know the enigmatic man behind the reputation, it’s as if the jagged pieces of both of their pasts slowly begin to fit together . . . until something so unexpected happens that it changes the course of their relationship―and both their lives―forever. The Masterpiece is perfect for fans of: Clean contemporary romance Christian women’s fiction Riveting stories with themes of faith and forgiveness “Rivers deftly threads Roman’s and Grace’s lives together as they tiptoe around their emotional scars, eventually shifting into a dance of tentative steps toward a love neither can resist. Fans of Christian romance will delight in this tale of salvation through love.” ― Kirkus Reviews “Richly detailed characters with traumatic pasts are woven together with biblical truths and redemptive themes. . . . This is an amazing, beautifully written tale to be savored and pondered and shared with others.” ― Romantic Times “Readers will marvel at Rivers’s storytelling arc encompassing the reconciliation of gritty past misdeeds and the work in progress of a life of forgiveness.” ― Booklist “Fans of Francine Rivers will eagerly devour The Masterpiece and find exactly what they are looking for: a beautifully written story of faith, romance, and the power that true freedom can bring.” ― Bookreporter